The Long-Term Effect of Radical Prostatectomy on Erectile Function, Urinary Continence, and Lower Urinary Tract Symptoms: A Comparison to Age-Matched Healthy Controls. (5th February 2017) - Mohamad Al-Ali, Badereddin; Ponholzer, Anton; Augustin, Herbert; Madersbacher, Stephan; Pummer, Karl
Abstract : Introduction . To analyze the impact of radical prostatectomy (RPE) on erectile function and lower urinary tract function in comparison to age-matched healthy men. Materials and Methods . Patients who underwent radical retropubic prostatectomy completed questionnaires containing the IIEF-5, the Bristol female LUTS questionnaire, and the International Prostate Symptom Score (IPSS). Results . Patients after RPE were included (n = 363 ). Age-matched healthy men (n = 363 ) were included. The mean IIEF-5 of patients aged 61–70 yrs after RPE was 10.4 ± 6.6 versus 18.8 ± 5.3 in the control cohort; the respective values for men aged 71–80 yrs after RPE were 7.2 ± 6.5 versus 13.6 ± 7.7 in the control cohort. Urinary incontinence after RPE was reported in 41.9% (61–70 years) and 37.7% (71–80) versus 7.5% and 15.1% in the control cohort. The mean IPSS of patients after RPE aged 61–70 yrs was 5.0 ± 4.4 versus 5.5 ± 4.9 in the control cohort; the respective values for men aged 71–80 yrs were 6.0 ± 4.9 versus 7.5 ± 5.7 in the healthy cohort. Conclusions . The negative effect of radical prostatectomy on erectile and urinary incontinence remains substantial. The physiologically declining erectile and lower urinary tract function with ageing reduces the difference between healthy men and those after surgery. Healthy men have a higher IPSS presumably due to the presence of bladder outlet obstruction.